Analysis Of The Effect Of Non Performing Loan (Npl), Loan Deposit Ratio (Ldr), Operating Expenses (Bopo), And Net Interest Margin (Nim) On Return On Asset (Roa) (Case Study Of Bank Negara Indonesia 2002-2023) - Herdini Nur Islamiati; Surya Raharja (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the effect of Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Operational Costs to Operating Income (BOPO), and Net Interest Margin (NIM) on Bank Negara Indonesia (BNI), as measured by Return On Asset (ROA) The research uses data obtained from the Annual Financial Statements of Bank Negara Indonesia from 2022 to December 2023, with 86 samples. The analysis technique used is multiple linear regression analysis. Before applying multiple linear regression, classical assumption tests were conducted first. The results of the study show that NPL has a negative and significant effect on ROA. Meanwhile, LDR has a negative and significant effect on ROA, BOPO also has a negative and significant effect on ROA, and NIM has a positive and significant effect on ROA.